Local Probiotic Lactobacillus crispatus and Lactobacillus delbrueckii Exhibit Strong Antifungal Effects Against Vulvovaginal Candidiasis in a Rat Model - Li, Ting; Liu, Zhaohui; Zhang, Xu; Chen, Xi; Wang, Suxia (Frontiers in Microbiology, 2019)
A comprehensive knowledge of the vaginal ecosystem is critical for the development of successful approaches to the treatment of infections. The role of Lactobacilli in preventing vulvovaginal candidiasis (VVC) is controversial. In this study, we investigated the therapeutic effects and mechanism of Lactobacillus (L.) crispatus or delbrueckii on vaginitis caused by Candida albicans in a Sprague–Dawley rat model. A microbiological evaluation was performed by Gram staining and fungal colonies were enumerated. The antifungal efficacy of the two Lactobacillus strains was assessed by hematoxylin and eosin staining, transmission electron microscopy (TEM), and immunohistochemical detection of interferon-γ (IFN-γ), interleukin (IL)-4, IL-17, and epithelial-derived IgG (RP125). Our in vitro results showed that the inhibitory activity against Candida colony-forming unit (CFU) counts was demonstrated by the two Lactobacillus strains (P < 0.001). Our results indicated that Lactobacillus administration played an indispensable role in maintaining the immune homeostasis, and decreasing the Th1/Th2 ratio (IFN-γ/IL-4) by regulating the epithelial secretion of cytokines that inhibit epithelial proinflammatory cytokine release, while increasing epithelial-derived IgG expression (P < 0.05), suggesting antibody-mediated protection. Our results implicate L. crispatus and L. delbrueckii as a potential adjunct biotherapeutic agent in women with VVC, especially for those with drug resistance, adverse effects or contraindications when using antifungal agents. Further large, long-term, well-planned clinical studies should be performed in clinical practice to determine their clinical potential of L. crispatus and L. delbrueckii as an adjunct treatment for VVC.